Tourism, border politics and the fault lines of mobility - Bianchi, R. V.; Stephenson, M. L. * (Routledge, 2019)
This chapter examines the contradictions that mark the intersections between the right to the freedom of movement and travel, and the right to tourism. While tourism is celebrated as an instrument of economic development, force for peace and a marker of global citizenship, the intensification of securitized bordering practices has accentuated severe inequalities between those deemed to lack the right credentials for travel and those whose mobility is defined as legitimate. The argument presented in this chapter repudiates the normative view of tourism as an apolitical phenomenon removed from the broader realm of mobility politics and structural determinants of immobility. In doing so it highlights a central paradox of international tourism, whereby growing institutional support for the right to tourism coincides with and potentially reinforces calls for the securitization of borders to be strongly enforced - at home and at the destination itself